The king of late night - Gutfeld, Greg (Threshold Editions, 2023)
"Greg Gutfeld is back with a hilarious essay collection about how he destroyed the mainstream late night landscape of heavyweights and became host of the #1 late night show in all of television. With his signature wit and whip-smart humor, Greg reveals never-before-told stories of his upbringing and early career, what it's like going head-to-head with the liberal media, and what it took to flip the script on the comedy landscape. How did the former health magazine editor take a show in a throwaway time slot in the middle of the night and turn it into a cult classic? And how did that show, Redeye, catapult Greg to The Five, the most watched show on TV, and GUTFELD!, his own late-night spot, with millions of viewers each night? Buckle up, because this story is one hell of a ride, especially if Greg is driving"--